The need for education about death in medical practice (2023)
Colombia is one of the leading countries in the world regarding regulations and rights at the end of life. Currently, there is legislation on access to palliative care, limitation of therapeutic effort, euthanasia, euthanasia in children and adolescents, conscientious objection for doctors, and medically assisted suicide is decriminalized. Meanwhile, the remaining Latin American countries are just beginning the discussion about dignified death. Among many reasons for this delay, one of them is that it begins with the most controversial of issues, euthanasia, instead of focusing on humanizing the end of life.